2009
DOI: 10.1186/1471-2350-10-125
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor polymorphisms with the risk of prostate cancer in the Han population of Southern China

Abstract: BackgroundMolecular epidemiological studies have shown that gene polymorphisms of vitamin D receptor (VDR) are associated with prostate cancer risks. However, previous results from many molecular studies remain inconsistent.MethodsBlood samples were collected from 122 prostate cancer patients and 130 age-matched control subjects in the Han population of Southern China. The differences of VDR gene polymorphism between cancer cases and controls were determined by PCR-RFLP, examiming FokI (exon 2), BsmI, Tru9I, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Prostate cancer is among those with reported association in American (Taylor et al, 1996), Chinese (Bai et al, 2009) and Koreans (Ohi et al, 2014). In addition, Gc polymorphisms were demonstrated on a meta-analysis for their association with skin cancer susceptibility in European (Zhaoi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is among those with reported association in American (Taylor et al, 1996), Chinese (Bai et al, 2009) and Koreans (Ohi et al, 2014). In addition, Gc polymorphisms were demonstrated on a meta-analysis for their association with skin cancer susceptibility in European (Zhaoi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The BsmI or FokI SNPs in VDR have been associated with breast, bladder, renal, carcinoma, and cutaneous malignant melanoma and nonmelanoma skin cancer (Mittal et al, 2007;Gandini et al, 2009;Tang et al, 2009;Arjumand et al, 2012). These polymorphisms were also recognized as risk factors of hepatocellular, head and neck, thyroid, prostate, and colorectal cancers (Liu et al, 2005;Mishra et al, 2005;Bai et al, 2009Bai et al, , 2012Penna-Martinez et al, 2009;Falleti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is a silent mutation and does not affect the amino acid sequence of the encoded protein. However, it is thought that the 3′-UTR of the VDR gene is involved in the regulation of mRNA stability, and therefore polymorphisms of this region (such as Bsm I and Apa I) are involved in the degradation of VDR mRNA and consequently reduce receptor density [12,15,19]. These polymorphisms might affect splicing by changing hnRNA structure, which could influence transcription, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, Bsm I, Apa I, Taq I, Fok I and Cdx2 are the most studied polymorphisms. It has been reported that these polymorphisms are associated with various diseases including psoriasis, diabetes mellitus and cancers [10,11,12,13,14,15,16]. Up to date, there is only one study showing that the Apa I polymorphism of the VDR gene is associated with vitiligo and might play a role in the etiopathogenesis of the disease [17].…”
Section: Introductionmentioning
confidence: 99%